2009
DOI: 10.1007/s11205-008-9427-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Community Life Among Rural Residents: An Integrated Model

Abstract: Quality of community life, Community satisfaction, Community attachment, Housing satisfaction, Spillover effects,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 25 publications
2
27
1
Order By: Relevance
“…In addition, it also had indirect effects on RSTD through the two constructs of "perceived benefits of tourism development" and "perceived costs of tourism development". These conclusions are consistent with the prior studies of Auh and Cook (2009) and Jurowski et al (1997). The causality among theses constructs relied on the logics: those who express more community attachment may also be more concerned with tourism and poverty alleviation, which in turn will impact their satisfaction with tourism development.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, it also had indirect effects on RSTD through the two constructs of "perceived benefits of tourism development" and "perceived costs of tourism development". These conclusions are consistent with the prior studies of Auh and Cook (2009) and Jurowski et al (1997). The causality among theses constructs relied on the logics: those who express more community attachment may also be more concerned with tourism and poverty alleviation, which in turn will impact their satisfaction with tourism development.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…The causality among theses constructs relied on the logics: those who express more community attachment may also be more concerned with tourism and poverty alleviation, which in turn will impact their satisfaction with tourism development. According to Auh and Cook (2009), residents who live for more than 10 years in a community were more likely to be emotionally attached to the community and expressed more community satisfaction than short-term residents. In the five poor villages of this study, more than 69% of the residents have lived in local community for more than 10 years.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parkes et al (2002) showed that people in residence over five years were less likely to exhibit decreased neighbourhood satisfaction than others, suggesting that neighbourhood attachment increase in the five to ten years residence period including in the urban area. Moreover, Auh and Cook (2009) highlight that, residents who lived more than 5 years in the areas are likely to be emotionally attached to the place and express more community knowledge and pleasure than short-term residents. It is not just the identity of a place that is important, but also the identity that a person or group has with that place in particular whether they are experiencing it as an insider or an outsider (Relph, 1976).…”
Section: Resultsmentioning
confidence: 99%